2008
DOI: 10.1107/s0108767308096414
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the plasma membrane proton pump

Abstract: DsbB is an E. coli membrane protein that oxidizes DsbA, the primary protein disulfide donor present in the periplasm. To understand how disulfide bonds are generated and introduced into secreted proteins, we determined the crystal structure of DsbB in a complex with DsbA and endogenous ubiquinone at 3.7 Å resolution. The first structure of DsbB revealed that DsbB contains the four-helix bundle scaffold in the transmembrane region and one short membrane-parallel α-helix in the long periplasmic loop. Strikingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 0 publications
1
97
0
Order By: Relevance
“…Although no crystal structure is available for a P4-ATPase, these proteins are probably not very different in folding from other members of the P-type ATPase family, as suggested by the fact that (i) all P-type ATPases including P4-ATPases have conserved core sequence segments that are essential for catalysis [98,109], and (ii) all crystallized P-type ATPases show a very similar tertiary structure despite their varying TMD numbers and diverse substrates ranging from protons to heavy metals [108,110]. Thus, assuming an analogous transport mechanism for P4-ATPases as for the SERCA pump, the phospholipid would occupy the place of the counter-ion and therefore be bound in the E2P conformation at the exoplamic side of the membrane and released in the transition step to E2 on the cytosolic side.…”
Section: General Catalytic Cycle Of P-type Atpasesmentioning
confidence: 95%
“…Although no crystal structure is available for a P4-ATPase, these proteins are probably not very different in folding from other members of the P-type ATPase family, as suggested by the fact that (i) all P-type ATPases including P4-ATPases have conserved core sequence segments that are essential for catalysis [98,109], and (ii) all crystallized P-type ATPases show a very similar tertiary structure despite their varying TMD numbers and diverse substrates ranging from protons to heavy metals [108,110]. Thus, assuming an analogous transport mechanism for P4-ATPases as for the SERCA pump, the phospholipid would occupy the place of the counter-ion and therefore be bound in the E2P conformation at the exoplamic side of the membrane and released in the transition step to E2 on the cytosolic side.…”
Section: General Catalytic Cycle Of P-type Atpasesmentioning
confidence: 95%
“…Numerical estimate of membrane protein from solution 10. Calculate GFP concentration in mg ml −1 in 100 μl of solution (membranes or buffer) as follows:…”
Section: Numerical Estimate Of Whole-cell Overexpressionmentioning
confidence: 99%
“…Although more structures of eukaryotic membrane proteins have been determined using material isolated from heterologous overexpression in the methylotrophic yeast Pichia pastoris, this difference is likely due to the popularity of P. pastoris because of its ability to produce a large biomass during fermentation with methanol 8 . However, recent work has demonstrated that S. cerevisiae is also a suitable host for obtaining enough material that will give high-resolution membrane protein structures 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The first model is an extrapolation from the structure of the H + (P3A) transporters [18]. These transporters also lack the anionic and polar residues that form the ion-binding sites in the Ca and Na/K transporters.…”
Section: The Proton Transporter Modelmentioning
confidence: 99%